“Music of Sound”: Using Existing Sonic Environments to Develop Inclusive, Experiential, and Collaborative Pedagogy in Malaysia - Beng, Tan Sooi; Chee, Toh Lai (MUSICultures, 2023)
Music of Sound (MOS) pedagogy promotes the learning of musical concepts and creative expression using everyday objects, body parts, and one’s voice. The authors discuss the experiential, collaborative, and place-based approaches they have developed in MOS projects for schoolchildren of different ethnic, religious, and social backgrounds in Malaysia over the last two decades. Ensemble work in skill training, field research, and collective composition resulting in site-specific workshop performances enhances interethnic cohesion among children. Tertiary students who are involved in facilitation experience multiple kinds of musical knowledge and the potential of collaborating with multiethnic communities of practice.